Corporate Governance Practice for Tourism Small and Medium-Sized Enterprises in Malaysia - Mohd Shariff, Nurhazani; Zainol Abidin, Azlan (2014)
The Tourism Small and Medium-Sized Enterprises (TSMEs) make a significant portion of entrepreneurial enterprises in Malaysia, and as a matter of fact play a big role as the backbone in the Malaysian tourism industry. Good corporate governance has been proven as a mechanism to increase companies' performance and since corporate governance also plays a vital role in the small firms including entrepreneurial, this study intends to examine the corporate governance practices in TSMEs namely ownership and board structure, conflict of Interest, stakeholders, social responsibility, remuneration and transparency. A number of 229 respondents consisted OF board of directors and top management of TSMEs were asked to indicate the importance of corporate governance practices and to determine the component of best practices for the TSMEs. The findings highlight that all the six corporate governance practices significantly derived as important component for the TSMEs. At present, there has been limited study on corporate governance in TSMEs. Hence. these findings would contribute towards considering these best practices as a vital role in managing TSMEs in achieving their strategies and objectives.